2023
DOI: 10.1093/ejcts/ezad256
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary function in lung cancer patients after segmentectomy or lobectomy: a retrospective, non-intervention, observation study

Abstract: OBJECTIVES Pulmonary segmentectomy (SE) became an increasingly popular method for resection of early-stage lung cancer. This study aims to compare the impact of single SE (SSE), multiple SE (MSE) and lobectomy (LE) on postoperative pulmonary function (PF) in patients with non-small cell lung cancer (NSCLC). METHODS Medical records of a total of 1284 patients who underwent LE (n = 493), SSE (n = 558) and MSE (n = 233) at Shang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Based on existing reports regarding the impact of different types of lobectomy on lung function, except for the RML, there are no significant differences in the long-term effects on lung function parameters following resections of various lung lobes 6 , 7 , 9 . For this phenomenon, our study may provide a more detailed explanation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on existing reports regarding the impact of different types of lobectomy on lung function, except for the RML, there are no significant differences in the long-term effects on lung function parameters following resections of various lung lobes 6 , 7 , 9 . For this phenomenon, our study may provide a more detailed explanation.…”
Section: Discussionmentioning
confidence: 98%
“…Theoretically, the postoperative lung function of patients can be predicted using the number of functional lung segments removed, i.e., predicting postoperative FEV1 = preoperative FEV1 × (1 − the number of functional lung segments intended to be removed / total number of functional lung segments) 4 , 5 . But many studies have shown that this calculation method underestimates the patient’s long-term lung function 6 , 7 . These suggest that compensatory mechanisms play a crucial role in the postoperative recovery process for lung resection patients.…”
Section: Introductionmentioning
confidence: 99%
“…For NSCLC up to 2 cm, Bao et al. ( 30 ) and Ji et al. ( 29 ) reported that segmentectomy shows less loss of lung function than lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary nodule (PN) is a round or irregularly shaped lesion less than or equal to 3 centimeters in diameter in the lungs, which appears on imaging as a shadow of increased density, with clear or unclear borders, and may be single or multiple [1] .With the advancement of computed tomography (CT) technology and the widespread implementation of screening programs targeting high-risk groups, including individuals susceptible to lung cancer, the detection of small pulmonary nodules has seen a signi cant surge in recent years [2] . Studies indicate that PN is detected in approximately one-third of individuals undergoing routine chest CT screening or diagnostic tests for various clinical purposes [3] .Compared to PN ,a speci c type known as ground glass nodules (GGN) carries a higher risk of malignancy and is closely associated with lung cancer [4] .Current treatment primarily involves surgical resection and subsequent monitoring [5,6] .High-risk nodules undergo a biopsy to ascertain their benign or malignant nature before surgical resection is considered.However, this approach may lead to complications such as pneumothorax, hemoptysis, and decreased lung function due to the removal of lung lobes [7] .Choosing between biopsy and surgery for non-cancerous nodules with medium to low risk can lead to excessive treatment, strain on healthcare resources,prolonged follow-ups,and increased mental stress,anxiety,and depression [8] .…”
Section: Introductionmentioning
confidence: 99%